OPTIMASI DAN ANALISA KADAR TOTAL PIGMEN KLOROFIL DALAM FORMULA MASKER GEL PEEL OFF EKSTRAK ETANOL KULIT BUAH SEMANGKA KUNING (Citrullus lanatus Thunb) - Eka Purwanto, Ungsari Rizki; Ariani, Lilies Wahyu (Media Farmasi Indonesia, 2018)
Most of the yellow watermelon skin only becomes waste. Yellow watermelon peel can be processed into a product so that it can still be utilized. The ability of watermelon peel to inhibit the Staphylococcus aureus bacteria and its ability as an antioxidant, can create the idea of a peel off gel mask product. The purpose of this study was to determine the optimum composition of Polyvinyl Alcohol (PVA) as a film forming layer and Hydroxypropyl Methylcellulose (HPMC) as a gelling agent for the physical properties of peel off gel mask product. Yellow watermelon skin extraction was carried out by remaceration with ethanol96% solvent combination and d-α-tocopherol. The response parameters used in the optimization assessment of the preparation are dispersion, adhesion, pH, dry time. The optimum formula is obtained based on analysis with Design Expert 10.0 software. The optimum formula of peel off gel mask ethanol extract of yellow watermelon peel had dispersion dameter of 4.77 cm; adhesion of 3,87 seconds; dry time was 5.98 minutes and pH was 5.90. This formula can maintain chlorophyll levels from watermelon skin extract in a gel peel off mask.